The role of parental status and involvement in sentence length decisions: a comparison of men and women sentenced to prison - Tasca, Melinda (Crime & delinquency, 2019)
Drawing upon familial paternalism theory, this study explores the effects of parental status and involvement on prison sentence length among men and women. To carry out this research, we relied on a combination of official and self-report data on 919 offenders sentenced to prison in Arizona. Results revealed that parents were not sentenced significantly differently from offenders without children; although women and mothers were punished more severely than their male counterparts. In addition, mothers who lived with their children before arrest received shorter prison terms than mothers who were uninvolved in their lives. Parental involvement was not a significant predictor of fathers’ prison sentences, however. This study illuminates the complex interplay between parenthood, gender, and sentencing.